RADIOACTIVE WASTE STORAGE AS AN ELEMENT OF NATIONAL SECURITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The presence of numerous nuclear power plants on the European continent is a guarantee of the energy security of the countries of the continent. At the same time, the problem of storing spent nuclear fuel is also deepening, because fewer and fewer manufacturers are engaged in its processing. The use of radioactive isotopes in medical diagnostics and treatment is also increasing, as well as in many sectors of the economy. But for now, the problem of storing these radioactive materials is lagging. The prospects for storing these materials have been examined and based on the data on the presence of radioactive waste, a systematic proposal for short-term and long-term storage of these materials has been made. The study is in its initial phase and the values are yet to be specified and a more precise proposal for storing nuclear waste is to be made.